2005
DOI: 10.1111/j.1572-0241.2005.40785.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Breastfeeding in Postpartum Disease Activity in Women with Inflammatory Bowel Disease

Abstract: A significant number of women with IBD do not breastfeed their children. Any relationship between breastfeeding and disease activity may be more a consequence of discontinuation of IBD therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(67 citation statements)
references
References 14 publications
2
62
0
3
Order By: Relevance
“…It was initially believed that an increase of disease flare occurred in both the first trimester and post-partum, but timing of a flare appears to more related to disease activity at conception and at term. Moreover, disease flare is often related to discontinuation of medical therapy (first trimester) or resuming smoking after delivery (post-partum) [2,11,31] . Active disease at conception can be associated with a worse prognosis.…”
Section: Ucmentioning
confidence: 99%
See 1 more Smart Citation
“…It was initially believed that an increase of disease flare occurred in both the first trimester and post-partum, but timing of a flare appears to more related to disease activity at conception and at term. Moreover, disease flare is often related to discontinuation of medical therapy (first trimester) or resuming smoking after delivery (post-partum) [2,11,31] . Active disease at conception can be associated with a worse prognosis.…”
Section: Ucmentioning
confidence: 99%
“…There have been some reported associations between nursing and increased disease activity, but this is unclear whether this is related to disease course or cessation of medication. Kane et al [31] found the odds ratio (OR) of disease flare for women who breastfeed was 2.2 (95% CI: 1.2-2.7) compared to those who did not breastfeed. However, once medication discontinuation was factored in, the OR became nonsignificant.…”
Section: Nursingmentioning
confidence: 99%
“…An earlier study of 122 women with IBD who were followed after delivery found 43% of women experienced a postpartum flare, of which 64% had a history of breastfeeding for at least 1 month prior to flare onset, with the trend persisting among CD patients (OR: 2.1; 95% CI: 1.1-8.5) but not for UC (OR: 0.9; 95% CI: 0.34-2.5) when stratified [58]. However, after adjusting for the high proportion of women who stopped medications prior to delivery and breastfeeding, there was no statistically significant increase in disease exacerbation with breastfeeding.…”
Section: Postpartum Period and Breastfeeding In Ibdmentioning
confidence: 99%
“…The percentage of women with inflammatory bowel disease who breast-feed varies from 44.2% to 83.3% [28,29]. Breastfeeding is not associated with increased risk of disease exacerbation.…”
Section: Lactationmentioning
confidence: 99%